La fantasía infantil y el rol del padre en Un monstruo viene a verme. De la novela al cine - Canals-Botines, Mireia (Studi sulla Formazione/Open Journal of Education, 2019)
A Monster Calls, a novel by Patrick Ness, is based on the original idea of Siobhan Dowd, and it was adapted to the cinema by J.A. Bayona in 2016. This article explores how the cinematographic language presents the figure of the father. The study is based on the method of analysis based on the theories of Aumont and Marie and Lavandier. We will analyse the father’s role in relation to the child and the family structure, and we will see how the father’s non-presence creates alternative survival situations for the child. Analysis tools will be used to establish a criterion to examine the father’s character, with the support of the shooting script, the storyboard and the novel.